ANALISIS IMPLEMENTASI RENCANA STRATEGIS DAN RENCANA OPERASIONAL DALAM MENINGKATAN MUTU PENDIDIKAN DI ERA PEMBELAJARAN MENDALAM - Arif Rahman; Hadani; Raihani Rahma; Rika Yuliani; Dewi Ayu Ratna Adi Juwita; Ahmad Suriansyah; Ratna Purwanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the implementation of the Strategic Plan and Operational Plan in improving educational quality in the era of deep learning at one public elementary school in Tanah Laut Regency. The background of this research is the importance of strategic and operational planning as fundamental instruments to ensure schools remain adaptive, effective, and oriented toward meaningful learning in response to the demands of 21st-century education. The purpose of this study is to analyze how the implementation of Strategic Plan and Operational Plan supports school management, instructional leadership, and continuous quality improvement. This research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and documentation, and were analyzed through data triangulation to ensure validity and reliability. The findings reveal that the effective implementation of Strategic Plan and Operational Plan is strongly influenced by visionary and instructional leadership of the principal, participatory communication, collaborative school culture, systematic monitoring and evaluation, and efficient resource management. Furthermore, the integration of strategic planning with instructional practices encourages adaptive curriculum development, professional growth of teachers, and improved learning processes aligned with deep learning principles. Continuous monitoring and evaluation enable schools to identify challenges, improve program effectiveness, and sustain quality improvement. In conclusion, the implementation of Strategic Plan and Operational Plan supported by strong leadership and systematic evaluation significantly contributes to sustainable school quality improvement in the deep learning era.